2012
DOI: 10.1016/j.ypmed.2011.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Using incentives to reduce substance use and other health risk behaviors among people with serious mental illness

Abstract: Introduction Serious mental illness (SMI) is associated with high rates of tobacco and other drug dependence, poor treatment compliance, obesity and low levels of physical activity, which have severe medical and psychosocial consequences. Interventions that effectively reduce these health risk behaviors among people with SMI are urgently needed. Methods Published reports from studies evaluating incentive-based treatments for promoting tobacco and other drug abstinence, treatment attendance, medication use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 81 publications
1
19
0
Order By: Relevance
“…This corresponds with some research that suggests that larger PFIs were more effective at changing health behaviour than small amounts (Lumley et al, 2009;Lynagh et al, 2011b;Sigmon and Patrick, 2012). The current study also adds another perspective on the utility of financial incentives for smoking cessation in disadvantaged groups which previous reviews have suggested is an efficacious and effective method of promoting smoking cessation amongst socially disadvantaged groups including low income pregnant women (Higgins et al, 2012;Lumley et al, 2009), illicit drug users (Sigmon and Patrick, 2012), and people with mental illness (Tidey, 2012). Further research regarding the acceptability, effectiveness and associated possible positive and negative effects of PFIs with disadvantaged groups is warranted.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This corresponds with some research that suggests that larger PFIs were more effective at changing health behaviour than small amounts (Lumley et al, 2009;Lynagh et al, 2011b;Sigmon and Patrick, 2012). The current study also adds another perspective on the utility of financial incentives for smoking cessation in disadvantaged groups which previous reviews have suggested is an efficacious and effective method of promoting smoking cessation amongst socially disadvantaged groups including low income pregnant women (Higgins et al, 2012;Lumley et al, 2009), illicit drug users (Sigmon and Patrick, 2012), and people with mental illness (Tidey, 2012). Further research regarding the acceptability, effectiveness and associated possible positive and negative effects of PFIs with disadvantaged groups is warranted.…”
Section: Discussionsupporting
confidence: 86%
“…They found that incentives were effective at encouraging cessation in four of five trials with opioid-maintained patients and that effect was moderated by incentive magnitude-the higher the incentive amount the more likely a positive outcome. Tidey (2012) found similar evidence for the effectiveness of PFIs for people with serious mental illness.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…67 Contingency reinforcement for reduced cotinine but not for group attendance was associated with reduction in urine cotinine and expired carbon monoxide in one study in smokers with schizophrenia. 68 Some evidence suggests NRT combined with monetary reinforcement for lower expired CO concentration is superior to placebo + contingency reinforcement for smoking reduction among smokers with schizophrenia while contingencies are in place.…”
Section: Resultsmentioning
confidence: 99%
“…Tidey 36 conducted a review of studies evaluating incentive-based treatments for promoting tobacco and other drug abstinence, treatment attendance, medication use and increased physical activity. They concluded that given the medical and psychosocial costs of tobacco and other drug use, treatment non-compliance and physical inactivity and the efficacy of incentive-based treatments for improving these behaviours, incentive-based treatments should be further developed and integrated into behavioural treatment programmes for people with serious mental illness.…”
Section: Carey and Careymentioning
confidence: 99%